FEASIBILITY OF USING LOW-PARAMETER LOCAL LLMS IN ANSWERING QUESTIONS FROM ENTERPRISE KNOWLEDGE BASE - Marcin BADUROWICZ; Stanisław SKULIMOWSKI; Maciej LASKOWSKI (Applied Computer Science)
This paper evaluates the feasibility of deploying locally-run Large Language Models (LLMs) for retrieval-augmented question answering (RAG-QA) over internal knowledge bases in small and medium enterprises (SMEs), with a focus on Polish-language datasets. The study benchmarks eight popular open-source and source-available LLMs, including Google’s Gemma-9B and Speakleash’s Bielik-11B, assessing their performance across closed, open, and detailed question types, with metrics for language quality, factual accuracy, response stability, and processing efficiency. The results highlight that desktop-class LLMs, though limited in factual accuracy (with top scores of 45% and 43% for Gemma and Bielik, respectively), hold promise for early-stage enterprise implementations. Key findings include Bielik's superior performance on open-ended and detailed questions and Gemma's efficiency and reliability in closed-type queries. Distribution analyses revealed variability in model outputs, with Bielik and Gemma showing the most stable response distributions. This research underscores the potential of offline-capable LLMs as cost-effective tools for secure knowledge management in Polish SMEs.